Public Private Partnership contracts in Mozambique and South Africa: managing risks and ensuring sustainability - Pequenino, Benjamim (Department of Commercial Law, 2023)
In the early 2000s, the world witnessed the emergence of a new variant of the juridical entity whose fundamental characteristic is the conjunction between public and private actors with the intention of delivering public infrastructures that otherwise would be impossible to realise. This new variant came to be known as the Public-Private Partnership (PPP). Since then, it has taken centre stage in development discourse assuming academic and practical importance due to the perceived role it plays in global development. Although research interest in PPP contracts has increased globally, only a few studies focus on the Southern Africa Development Community (SADC) region. The present study contributes by filling in this gap and providing a comparative perspective on the regimes of the PPP contract in Mozambique and South Africa. While PPPs may provide much needed infrastructure to meet the needs of end users, this often comes at considerable cost. The fiscal cost and distributional implications of PPPs are accentuated when compared with state borrowing. In addition, when it comes to risk management, all those risks that are supposedly transferred to a private operator are never truly transferred and, in the end, the government is always the residual risk holder should the PPP consortium fail. Far from freeing resources to be invested in other poverty reduction programmes, PPPs can absorb funds that could have been devoted directly to such programmes. In the end, rather than compensating for weak state capacity it places significant extra demands on it. These contradictions call into question the merits of promoting PPPs to overcome developing countries' public service financing gap, as the evidence clearly suggests that PPPs often have tended to be more expensive than their public procurement alternative, and in a number of instances they have failed to deliver the envisaged gains. The research in both jurisdictions has also analysed context-specific factors capable of jeopardising the successful implementation of PPP contracts. These include non-streamlined regulatory frameworks, state capacity constraints, weak integrity systems, and corruption. The key recommendation drawn from the research is that in order for the PPPs to be able to harness their full potential and deliver on expected gains, substantial regulatory and institutional reforms are needed in both jurisdictions studied.